Supermacroporous Composite Cryogels in Biomedical Applications - Saylan, Yeşeren (Gels, 2019)
Supermacroporous gels, called cryogels, are unique scaffolds that can be prepared by polymerization of monomer solution under sub-zero temperatures. They are widely used in many applications and have significant potential biomaterials, especially for biomedical applications due to their inherent interconnected supermacroporous structures and easy formation of composite polymers in comparison to other porous polymer synthesis techniques. This review highlights the fundamentals of supermacroporous cryogels and composite cryogels, and then comprehensively summarizes recent studies in preparation, functionalization, and utilization with mechanical, biological and physicochemical features, according to the biomedical applications. Furthermore, conclusions and outlooks are discussed for the use of these promising and durable supermacroporous composite cryogels.